Synthesis of Copolymer of Maleic Anhydride and Vinyl Acetate Using Antimony Oxide as Catalyst - PANDEY, A.K.; KUMAR, D.; PAL, R.S. (Asian Journal of Chemistry, 2010)
The copolymer of maleic anhydride and vinyl acetate was synthesized under different reaction conditions using antimony oxide as catalyst.